Measuring motivation among close-to community health workers: Developing the CTC Provider Motivational Indicator Scale across six countries - Vallières, Frédérique; Kok, Maryse; Mahmud, Ilias; Sarker, Malabika; Jeacocke, Philippa; Karuga, Robinson; Limato, Licia; Kea, Aschenaki Z.; Chikaphupha, Kingsley; Sidat, Mohsin; Gilmore, Brynne; Taegtmeyer, Miriam (BMC, 2022)
This article was published in Human Resources for Health by BMC [ © The Author(s). 2020 Open Access This article is licensed under a Creative Commons Attribution 4.0 International License,] and the definite version is available at: https://doi.org/10.1186/s12960-020-00495-7 The Journal's website is at: https://human-resources-health.biomedcentral.com/articles/10.1186/s12960-020-00495-7